Targeted phototherapy for skin diseases - Sa’adatul Huriyah Arief Budiyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Phototherapy is a therapeutic strategy in dermatology for treating several skin diseases.Conventional phototherapy has some disadvantages, hence a targeted phototherapy that emitsselective laser or ultraviolet (UV) light and targets specific area of affacted skin has been developed.Targeted phototherapy is considered to be more aggressive and has higher efficacy. Severaltargeted phototherapy devices emit one or several types of light. The use of targeted phototherapyhas been studied in vitiligo, psoriasis, eczema, keloid, hypopigmented scar or striae alba, andoral lichen planus.